GLIAL CELLS, BLOOD BRAIN BARRIER AND CYTOKINES IN SEIZURES: IMPLICATIONS FOR THERAPEUTIC MODALITIES - Šutulović, Nikola B; Marchini, Simone Pietro; Šuvakov, Sonja R; Hrnčić, Dragan R (Medicinski podmladak, 2018)
Epilepsy is a chronic, common, neurological disorder marked by transient, paroxysmal and hypersynchronous activity of the brain neurons, behaviorally manifested as seizures. It is developed through the process of epileptogenesis which alters neuronal excitability, establishes critical interconnections and develop neuronal hyperexcitability and degeneration, as well as the neuronal network reorganization as its main mechanisms. There are a number of different mechanisms of epileptogenesis, including neuroinflammation as a recently highlighted important novel mechanism. In this review paper, our focus will be to light up the latest findings about neuroinflammation as a pathogenic factor in epileptogenesis. Neuroinflammation is characterized by the structural and functional alteration of the CNS glial cells and peripherally derived immune cells with the presence of blood-brain barrier (BBB) dysfunction as main mechanisms. Disequilibrium in the CNS microenvironment is often followed by increased synthesis of proinflammatory cytokines (IL-6, IL-1β, TNF-α, IFN-γ) and chemokines. The interplay between glial alteration, BBB dysfunction, cytokines and chemokines establish a positive feedback cascade for further epileptogenesis. It is still unclear if neuroinflammation is causing epileptogenesis or whether in a consequence of that, but, there are clear findings about positive feedback between these two processes. This interconnection could be a helpful key to better target therapeutic treatment of neuroinflammation for providing beneficial effects for patients with epilepsy. Key words: epilepsy, epileptogenesis, neuroinflammation, glial alteration, BBB dysfunction, cytokines, chemokines